(untitled) (Research, Society and Development, 2025)
Introduction: Religiosity, understood as the connection between the human and the divine, reflects the culture and values of a people. In Goiás, faith and tradition intertwine in popular and religious manifestations that shape the collective imagination. In this context, the poet Cora Coralina, in Vintém de Cobre, reveals an intimate portrayal of Goian culture, permeated by religiosity, everyday life, and spirituality. Objectives: To analyze the work Vintém de Cobre by Cora Coralina, identifying representations of Goian cultural and religious traditions. Specifically, the study sought to recognize religious traits, cultural manifestations, and the author’s role as a preserver of Goian identity. Methodology: A qualitative approach was adopted, with an interpretative reading of Vintém de Cobre, highlighting symbols, metaphors, and passages related to religiosity and daily life. The analysis was based on a bibliographic review and literary interpretation, without human involvement. Results: It was found that Cora Coralina expresses popular Catholicism and religious syncretism as pillars of Goian culture. In her verses, Catholic faith—once central—shares space with modernity, yet remains alive in customs and values. The author also introduces references to spiritism and everyday spirituality, especially by transforming the craft of confectionery into a transcendental and creative act. Conclusion: Vintém de Cobre translates Goian religiosity and spirituality as living expressions of culture. Faith, even redefined by modernity, endures as a moral and identity force. Spirituality in Cora Coralina emerges from simple gestures, uniting the sacred and the everyday in poetry of resistance and transcendence.